Biomass-derived phosphorus-doped hierarchical porous carbon fabricated by microwave irritation under ambient atmosphere with high supercapacitance performance in trifluoroacetic acid electrolyte. (January 2023) - Meng, Xianxin; Zhang, Deyi; Wang, Bing; He, Yulian; Xia, Xu; Yang, Biao; Han, Zhiyong
Abstract: Improving energy density while minimizing the cost is significant for boosting the commercial application of supercapacitors. In this paper, a facile microwave irradiation method is successfully developed for converting biomass into a phosphorus-doped hierarchical porous carbon with high specific surface area, good conductivity, and enhanced wettability within 5 min under ambient atmosphere. The prepared material releases a high specific capacitance of up to 297.1 F g −1 at a current density of 1 A g −1 within a wide voltage window of −1–0.5 V in a newly developed TFA electrolyte. The symmetric supercapacitor devices assembled using the prepared material and the TFA electrolyte can be stably operated at 1.5 V and exhibit high capacitance retention of up to 94.9 % after 30, 000 cycles. A nearly 2.5-fold improvement in energy density (16.5 Wh kg −1 at a power density of 375 W kg −1 ) is achieved for the assembled devices only by replacing the traditional H2 SO4 electrolyte with the newly developed TFA electrolyte. By employing the developed microwave irradiation method with high efficiency and low cost and the newly developed TFA electrolyte, excellent performance and low cost can be achieved simultaneously for supercapacitors, which provides a promising strategy to boost the commercial application of supercapacitors. Graphical abstract: Unlabelled Image Highlights: A microwave irradiation method was developed for converting biomass into PHPC. PHPC can be fabricated within 5 min under an ambient atmosphere. A TFA electrolyte is successfully developed to improve the energy density of SC. A 2.5-fold improvement in energy density was achieved by using the TFA electrolyte.